SYNTHESIS OF NOVEL 1,2-DIOL CONTAINING AZO DYES FOR POLYMERIC SUBSTRATES - Khadim Sheikh, Hamdullah; Hassan Kazmi, Mehdi (Journal of the Chilean Chemical Society, 2017)
Two novel 1,2-diol containing azo dyes have been synthesized for application on polymeric textile substrates. We used multistep synthesis scheme which involved selectively bonding azo chromophore with glycerol moiety such that only one alcohol out of the three gets bonded to the chromophore while rest two remain unchanged. The 1,2-diol moiety, common in both dyes, is responsible for forming hydrogen bonds with polar sites on a polymeric substrate. The molecular structure of the final molecule and synthesized intermediates were elucidated by UV/Vis, FT-IR, MS (EI, ESI, and CI) and 1H-NMR spectroscopic techniques. Dyes were applied to polyester and nylon 66 fabrics as disperse dyes by exhaust dyeing method and furnished good to excellent fastness properties on both of them.